Electronic Properties of Transition‐Metal‐Decorated Silicene. Issue 18 (9th October 2014) - Lee, Youngbin; Yun, Kyung‐Han; Cho, Sung Beom; Chung, Yong‐Chae
Abstract The electronic properties of 3d transition metal (TM)‐decorated silicene were investigated by using density functional calculations in an attempt to replace graphene in electronic applications, owing to its better compatibility with Si‐based technology. Among the ten types of TM‐doped silicene (TM–silicene) studied, Ti‐, Ni‐, and Zn‐doped silicene became semiconductors, whereas Co and Cu doping changed the substrate to a half‐metallic material. Interestingly, in cases of Ti‐ and Cu‐doped silicene, the measured band gaps turned out to be significantly larger than the previously reported band gap in silicene. The observed band‐gap openings at the Fermi level were induced by breaking the sublattice symmetry caused by two structural changes, that is, the Jahn–Teller distortion and protrusion of the TM atom. The present calculation of the band gap in TM–silicene suggests useful guidance for future experiments to fabricate various silicene‐based applications such as a field‐effect transistor, single‐spin electron source, and nonvolatile magnetic random‐access memory.